2017
DOI: 10.5935/1518-0557.20170020
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of assisted reproductive technology in overweight and obese women

Abstract: ObjectiveThe main objective of this study was to assess the prevalence of overweight and obesity among patients undergoing assisted reproductive technology (ART) in Latin America and its consequences on treatment outcomes.MethodsWe used the Latin American Registry of ART to obtain women's age and body mass index (BMI), cancellation rate, number of oocytes retrieved and embryos transferred, clinical pregnancy, live birth and miscarriage rates from 107.313 patients undergoing autologous IVF and ICSI during four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 35 publications
2
33
1
1
Order By: Relevance
“…We also did not find any relationship between BMI and IVF success which is in harmony with the results of a study conducted by MacKenna et al in Latin America. In the study by MacKenna which was conducted on a sample of women with a high prevalence of obesity, BMI did not influence the outcome of ART (27).…”
Section: Discussionmentioning
confidence: 92%
“…We also did not find any relationship between BMI and IVF success which is in harmony with the results of a study conducted by MacKenna et al in Latin America. In the study by MacKenna which was conducted on a sample of women with a high prevalence of obesity, BMI did not influence the outcome of ART (27).…”
Section: Discussionmentioning
confidence: 92%
“…There is no obesity patient in our group. The sudy of Antonio MacKenna etc showed that BMI does not influence the outcome of ART performed in women of Latin America (14). Also some study (15) showed that among women undergoing first FET with high-quality embryo transfer, obesity was associated with worse IVF outcomes, but not overweight.…”
Section: Discussion 11mentioning
confidence: 99%
“…However, the authors noted that one of the limitations of the study was the inability to adjust for patient race across BMI categories. In a study conducted in a Latin American population, MacKenna et al. (2017) did not observe a correlation of low weight with IVF outcomes.…”
mentioning
confidence: 81%
“…However, evidence of the effects of low BMI on ART outcomes is conflicting. On one hand, low BMI has been associated with a reduced probability of achieving pregnancy, increased risk of miscarriage and reduced live birth rate ( Wang et al , 2000 ; Wittemer et al , 2000 ; Veleva et al , 2008 ; Singh et al , 2012 ; Cai et al , 2017 ); on the other hand, several studies have found no effect on treatment outcomes ( Lashen et al , 1999 ; Fedorcsák et al , 2004 ; Li et al , 2010 ; Provost et al , 2016 ; MacKenna et al , 2017 ). Nevertheless, some studies report that patients with low BMI have worse clinical outcomes than patients with normal BMI, although these results were not statistically significant.…”
mentioning
confidence: 99%